MYOCARDIAL PROTECTION OF PERFLUOROCHEMICALS (FC-43) IMMERSION DURING ISCHEMIA - ANDO, Susumu; INOUE, Koichi; NOMOTO, Seiro; TAKABA, Toshihiro; HONDA, Osamu; SEKIGUCHI, Shigeaki; HANAFUSA, Yuji; OZAWA, Atsusi; YAMADA, Makoto; KADOKURA, Mitsutaka (Journal of The Showa Medical Association, 1995)
Topical cooling of the heart is an effective method of protection for the myocardium during ischemia, but it has some disadvantages. The disadvantages include phrenic nerve injury, uneven supply of the cardioplegic solution due to coronary spasm and damage to the epicardium. In order to avoid these cooling-related disorders, mild topical cooling was applied and the heart was immersed in FC 43 emulsion of perfluorochemicals (PFC) which has an excellent oxygen transport activity, in attempt to supply oxygen to meet the increasing demand for oxygen of the myocardium. The hemodynamic recovery was studied in 4 groups of isolated rat hearts, during ischemia for 60 minutes (group A) and 90 minutes (group B) at 30°C after cardioplegic arrest, two groups (A1 and B1) were not immersed in FC 43; the other two groups (A2 and B2) were immersed in FC 43. As a result, there are no significant differences in the hemodynamic recovery between group A2 and group A1. The 5 hearts in group B1 were unable to resume the beat after reperfusion. In contrast, all hearts of group B2 resumed the beat; the cardiac function was restored by more than 70%, and the results were significantly better (p<0.001) than in group B1. These results suggest the possibility that oxygen was supplied to the myocardium by immersion of the hearts in perfluorochemicals there by meeting the demand for oxygen of the myocardium in the state of ischemia and hypoxia with the aid of mild topical hypothermia.